The alternation of brain activity in frontal cortex with proficiency levels in trampoline athletes - Yamazaki, K.; Yamazaki, H.; Itoh, N. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: It is generally concerned to be difficult to discover the future skills development in beginner athletes, especially in the sports events that have a few athletes like the trampoline. Coaches have to predict, depending on their subjective evaluation, whether a beginner athlete will be a competent athlete having good potential and skills or not, in the athletes` early practical stage. If the coaches are able to know athletes` future skills in the early stage of the training process or athletes` skills development, it will provide them a lot more time to train athletes and improve their skills. In previous studies of motor learning which demonstrated the relationship between brain activity and motor learning, a brain activity will change according to process of motor learning. In this study, we hypothesized that there are some alternation of brain activities during the acquisition process of the trampoline jumping skills. To observe these alternations, we examined brain activities in frontal robe with motor imagery of trampoline jumping action. Methods: 3 trampoline athletes were voluntarily recruited for this study. To observe spacio-temporal brain activity in frontal lobe, we used optical topography ETG-7100 (Hitachi medical, co. ltd., Japan). Optical prove (22ch) were put on the forehead, and subjects kept rest for few minutes before the measurement. The measurement protocol consisted by 15blocks. Each block includes 30seconds resting state period and 30seconds stimulation period. During stimulation period, subjects imaged the scene that the subjects are jumping. Jumping variation includes following 3 jumps: straight jump, double back and double twist. Each jump was included 5times in 15blocks sequence. Results and Discussion: We analyzed the difference in brain activity according to subjects` completion of jumping skills. Brain activity in frontal cortex few changed in the jump variation which the subject has already completed. However, in the jump variation which the subject hasn`t complete yet, the frontal cortex brain activity significantly changed in many measurement channels. In previous study, in the process of motor learning alter the brain activity especially in supplementary motor area. Once the person acquired the movement, the brain activity observed in motor area changes to supplementary motor area that controls the movement based on memories. Thought we didn`t investigate about the brain activity by real body movement, we suggest that movement acquisition might change the brain activity.